Srolo Bzhtang, a traditional Tibetan medicine formula, inhibits cigarette smoke induced airway inflammation and muc5ac hypersecretion via suppressing IL-13/STAT6 signaling pathway in rats. (10th May 2019) - Jing, Linde; Su, Shanshan; Zhang, Dejun; Li, Zhanqiang; Lu, Dianxiang; Ge, Rili
Abstract: Ethnopharmacological relevance: Srolo Bzhtang (SBT), a traditional Tibetan medicine formula, was composed of three herbs, Solms-Laubachia eurycarpa, Bergenia purpurascens, Glycyrrhiza uralensis, and one lac, and was first documented in the ancient Tibetan medical work Four Medical Tantras (rGyud-bzhi) in the eighth century AD. It has been widely used to treat lung "phlegm-heat" syndromes such as chronic bronchitis and chronic obstructive pulmonary disease (COPD). Objective: The aim of this study was to evaluate the potential influences of aqueous extract of SBT on airway inflammation and mucus secretion and to reveal the underlying mechanism in a rat model of cigarette smoke (CS)-induced chronic bronchitis (CB). Materials and methods: Sixty male Sprague-Dawley rats were randomly divided to six groups: control (room air exposure), model (CS exposure), DEX (CS exposure and 0.2 mg/kg/day dexamethasone), and three SBT (CS exposure and 1.67, 2.50, and 3.34 g/kg/day SBT) groups. DEX and the three doses of SBT were administered by oral gavage every day for eight weeks. Pathological changes and mucus expression in the lung tissue were determined by hematoxylin and eosin (H&E), Alcian blue-periodic acid-Schiff (AB-PAS) and immunohistochemical staining. The levels of cytokines in bronchoalveolar lavage fluid (BALF) were assessed by ELISA. Western blot analysis and qRT-PCR were performed to explore the effects of SBT on the expression of IL-13, STAT6 and MUC5AC. Results: Pretreatment with SBT attenuated the TNF-α, IL-8, IL-13 expression levels in BALF and the inflammatory cell infiltration in bronchial walls and peribronchial lung tissue. SBT exhibited a dose-dependent downregulation of MUC5AC expression as assessed by AB-PAS and immunohistochemical staining. The protein and mRNA levels of IL-13, STAT6/p-STAT6 and MUC5AC were also downregulated by SBT preconditioning. Conclusion: These results for the first time demonstrated that SBT exhibited protective effects on CS-induced airway inflammation and MUC5AC hypersecretion, which might be related to the downregulation of the IL-13/STAT6 signaling pathway. Graphical abstract: fx1